Association between triglyceride-glucose (TyG) related indices and cardiovascular diseases and mortality among individuals with metabolic dysfunction-associated steatotic liver disease: a cohort study of UK Biobank - Yanan Qiao; Yue Wang; Cheng Chen; Yueqing Huang; Chunhua Zhao (Cardiovascular Diabetology)
Abstract Background Triglyceride-glucose (TyG) related indices, which serve as simple markers for insulin resistance, have been closely linked to metabolic dysfunction-associated steatotic liver disease (MASLD), cardiovascular disease (CVD), and mortality. However, the prognostic utility of TyG-related indices in predicting the risk of CVD and mortality among patients with MASLD remains unclear. Methods Data of 97,331 MASLD patients, with a median age of 58.0 years and free of CVD at baseline, were obtained from the UK Biobank. The TyG index, along with its combination with adiposity parameters (i.e. body mass index [BMI], waist circumference [WC], and waist-to-height ratio [WHtR]), were calculated. Cox proportional hazards models and restricted cubic spline (RCS) were performed to evaluate the associations between TyG-related indices and the risk of overall CVD, coronary heart disease (CHD), stroke, all-cause mortality, and cardiovascular mortality. Additionally, Harrell’s C-index, net reclassification index (NRI), and integrated discrimination improvement index (IDI) were used to assess the predictive performance of these indices. Results Over a median follow-up of 13.56 years, we identified 13,256 cases of overall CVD, 10,980 CHD, 2,926 stroke, 8,809 all-cause mortality, and 1,796 cardiovascular mortality. Compared with the lowest quartile of TyG-related indices, participants with MASLD in the high quartile of TyG-related indices had a significantly increased risk of incident overall CVD, CHD, stroke, and mortality. Specifically, the hazard ratios of occurring overall CVD in the fourth versus the first quartiles were 1.19 (95% confidence interval: 1.13–1.25) for TyG, 1.35 (1.28–1.42) for TyG-BMI, 1.33 (1.26–1.40) for TyG-WC, and 1.39 (1.32–1.46) for TyG-WHtR. RCS analyses indicated a nonlinear association of TyG with CVD outcomes (all P values for nonlinearity < 0.05), whereas there exhibited linear trends in TyG-BMI, TyG-WC, and TyG-WHtR with CVD outcomes (all P values for nonlinearity > 0.05, except for TyG-WC with stroke). Furthermore, TyG-WC and TyG-WHtR demonstrated the significantly higher C-index, NRI, and IDI in predicting risk of CVD and mortality in MASLD patients. Conclusion TyG-related indices, especially TyG-WC and TyG-WHtR, had significant predictive values for the risk of incident CVD and mortality in individuals with MASLD. TyG-related indices may serve as effective surrogate predictors of CVD and mortality in MASLD patients.